Are multiple multimetric indices effective for assessing ecological condition in tropical basins?. (March 2020) - Martins, Isabela; Macedo, Diego Rodrigues; Hughes, Robert M.; Callisto, Marcos
Highlights: Effectiveness of multimetric indices in environmental quality assessment. Ten MMIs from multiple continents were effective for evaluating ecological conditions. Even in protected areas, local disturbances affected biological condition. Abstract: The quality and availability of water resources in tropical watersheds are threatened by increased multiple use demands by human populations. Therefore, there is a need for cost-effective ecological indicators of water body status and trends. Multimetric indices (MMIs), based on responses of biological assemblages to anthropogenic disturbances, are excellent examples of such indicators and they have been applied globally. However, creating new MMIs for each water body or study area requires considerable analytical effort and hinders our ability to make regional or global comparisons. Therefore, we tested the effectiveness of 17 published benthic macroinvertebrate MMIs for assessing the environmental quality of a tropical anthropogenically least-disturbed river basin in the Neotropical Savanna (Brazilian Cerrado) biome. We tested those MMIs through use of macroinvertebrate data sampled at 40 stream sites in the Pandeiros River basin, Brazil. Disturbances in the basin were related to local factors such as pasture, garbage, and cropland in stream riparian areas. Index performance was tested by comparing precision, bias, responsiveness and sensitivity to anthropogenic pressures and stressors. Ten indices performed satisfactorily in evaluating the environmental condition of the basin. Therefore, we do not recommend developing new benthic MMIs for rapid environmental quality assessments. On the other hand, we do recommend using standard data collection methods for evaluating conditions throughout the biome.